2013
DOI: 10.1016/j.neuropharm.2013.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of angiotensin-(1-7) in ischemic stroke

Abstract: Previously we demonstrated that central administration of angiotensin-(1-7) [Ang-(1-7)] into rats elicits significant cerebroprotection against ischemic stroke elicited by endothelin-1 induced middle cerebral artery occlusion. Ang-(1-7), acting via its receptor Mas, reduced cerebral infarct size, and rats exhibited improved performance on neurological exams. These beneficial actions of Ang-(1-7) were not due to inhibition of the effects of endothelin-1 on cerebral vasoconstriction or effects on cerebral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
120
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 38 publications
8
120
0
Order By: Relevance
“…Reduction in baroreflex sensitivity and sympathetic activity is observed in Mas-null mice (Walther et al, 2000b). In addition Ang(1-7) and MAS provide a protective effect in models of stroke (Mecca et al, 2011;Regenhardt et al, 2013Regenhardt et al, , 2014a. MAS is present in select regions of the brain, which provides the structural basis for many effects produced by Ang (1)(2)(3)(4)(5)(6)(7) in the brain.…”
Section: G Pathophysiological Evidence Of Mas Receptor Interaction Wmentioning
confidence: 99%
“…Reduction in baroreflex sensitivity and sympathetic activity is observed in Mas-null mice (Walther et al, 2000b). In addition Ang(1-7) and MAS provide a protective effect in models of stroke (Mecca et al, 2011;Regenhardt et al, 2013Regenhardt et al, , 2014a. MAS is present in select regions of the brain, which provides the structural basis for many effects produced by Ang (1)(2)(3)(4)(5)(6)(7) in the brain.…”
Section: G Pathophysiological Evidence Of Mas Receptor Interaction Wmentioning
confidence: 99%
“…A growing body of evidence indicates that angiotensin-(1-7) and its receptor, the Mas receptor, are widely distributed in the central nervous system [20] and are potentially involved in the pathophysiology of brain diseases [9,[21][22]. However, to our knowledge, there is no report investigating the potential role of angiotensin-(1-7)/Mas receptor axis in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the antidiuretic action of Ang-(1-7) in Mas-KO mice is in agreement with the antidiuretic effect of Ang-(1-7) in water-loaded rats (Santos and Baracho, 1992). Diverging from many reports describing Mas-mediated anti-inflammatory effects in different tissues (Al-Maghrebi et al, 2009;da Silveira et al, 2010;El-Hashim et al, 2012;Giani et al, 2012;Jiang et al, 2012;Santos et al, 2012;Souza and Costa-Neto, 2012;Sukumaran et al, 2012;Chen et al, 2013;Feltenberger et al, 2013;Moore et al, 2013;Regenhardt et al, 2013;Wagenaar et al, 2013;Wang et al, 2013c;Acuna et al, 2014;Meng et al, 2014), in the kidney, a proinflammatory role for Ang-(1-7) and Mas was reported by using a model of unilateral ureteral obstruction in mice (Esteban et al, 2009). In contrast, anti-inflammatory and beneficial effects of Ang-(1-7) were observed in other models of kidney injury (Singh et al, 2010b;Moon et al, 2011;Bernardi et al, 2012;Giani et al, 2012;Harris, 2012;Chou et al, 2013;Santos et al, 2013b;Zhang et al, 2014).…”
Section: Mas-related G Protein-coupled Receptors and Mas In Cardiomentioning
confidence: 96%